2015
DOI: 10.18178/ijtef.2015.6.6.488
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Empirical Basis of Optimal Tax Burden in Georgia

Abstract: High speed of globalization has created inevitability of ensuring objectives of sustainable development of economics and optimally determined taxes can play very important role in it, which is the main factor for formation of tax burden. This in itself is an important leverage for achieving the sustainable development and prosperity of society. Generally, state regulates economy of the country through the taxes because it is the main tool for shaping the country's revenue part of the budget. The aim of the pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…In this regard, important reforms were implemented in Georgia, which reduced number of taxes from 21 to 6 (period:2004-2008), as well as tax rates were reduced. (Kbiladze, 2015). According to Georgian tax code, currently in country operates 6 types of taxes: 5state and 1 local.…”
Section: Results Of Tax Reform In Georgiamentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, important reforms were implemented in Georgia, which reduced number of taxes from 21 to 6 (period:2004-2008), as well as tax rates were reduced. (Kbiladze, 2015). According to Georgian tax code, currently in country operates 6 types of taxes: 5state and 1 local.…”
Section: Results Of Tax Reform In Georgiamentioning
confidence: 99%
“…After these reforms and improved administration process, tax revenues in Georgia has been increased in 2015 by 1,7 times in comparison with 2005.Tax burden parameter for the economy of Georgia ranges from 13.6% to 17.6%. (Kbiladze, 2015). Problematic issue for Georgia as well as for other countries in search of new tax paradigm arrangements is reduction of number of taxes, as well as rates of taxes.…”
Section: Results Of Tax Reform In Georgiamentioning
confidence: 99%
“…Now enterprises of our observation area should be divided into 10 parts (table 3). By given calculations, we can conclude that according to tax burden, 10% of low burden enterprises have 21.03% of whole burden, while also 10% of high burden enterprises have 33.7% of whole burden, which is 1.6 times higher than the lowest, whereas according to tax code of Georgia, enterprises irrespective of their size and type of activities are paying the same interest rate taxes (Kbiladze, 2015).…”
Section: Empirical Research Of Tax Burden Inequalitymentioning
confidence: 92%
“…Consider the following example. Let and̃= (1.0; 3.0; 5.0) be a triangular fuzzy number (TFN) describing fuzzy value of the growth rate of hypothetic economy, let̃= (0.32; 0.34; 0.35) be a TFN describing expert group-based computed by using (16), and = 0.737; = 1 in (13). It can be shown that the left hand side of (13) is an integrable fuzzy number-valued function of a real variable.…”
Section: An Examplementioning
confidence: 99%
“…Determination of the optimal size of tax burden is very important and difficult scientific and practical problem. The main goal of [16] is to determine the optimal of tax burden for the economy of Georgia. Optimally determined taxes can play very important role for sustainable development of economics.…”
Section: Introductionmentioning
confidence: 99%